Convex Accessibility Number of the Complements and Some Binary Operations of Graphs (European Journal of Pure and Applied Mathematics, 2024)
This study explores various aspects of the Convex accessibility number in graph theory, focusing on some binary operations namely cartesian product and strong product and complements of graphs. The computation of the Convex accessibility number of Cartesian product and Strong product of graphs is examined. Also, the Convex accessibility number of the complement of some known graphs is explored. Through these investigations, this study contributes to a deeper understanding of the Convex accessibility number in graph theory, offering insights into its behavior under different graph operations and complementation scenarios.